Development of a Multiplex PCR Assay for the Simultaneous Detection of Echinococcus spp. in Wild Canids in the Qinghai-Tibet Plateau Area of China - Xueyong ZHANG (University of Kafkas, 2021)
Infections of Echinococcus granulosus sensu stricto, E. multilocularis and E. shiquicus are usually prevalent or coendemic in wild canids in the Qinghai-Tibet Plateau area (QTPA) of China. Thus, an efficient method for the detection of infected hosts and the identification of Echinococcus species is needed. The present work aims to establish a multiplex PCR (mPCR) method that can simultaneously detect the three main Echinococcus species mentioned above, and provide technical support for the diagnosis, prevention and control of Echinococcus infection. Three pairs of specific primers were designed for this mPCR based on the Echinococcus mitochondrial genes in GenBank, and these primers were validated by specificity and sensitivity experiments and applied for simulated coinfection samples detection and filed samples. This mPCR method was able to successfully identify both simplex and mixed target Echinococcus spp. and generate expected amplicons of different sizes for each species. The sensitivity of this mPCR method was tested with serially diluted gene recombinant plasmid, and the results showed a detection threshold of less than 103 for both species. The specificity, which was assessed against 10 other parasites, was found to be 100%. The assay was also used on 15 simulated clinical samples, and the results confirmed the high reliability of the method, indicating that the mPCR method established in this study can be used to analyze clinical samples from the QTPA. This mPCR method has potential application in rapid detection, diagnosis and broad-scale screening and is expected to become a key technology for clinical detection and environmental monitoring.